Risk Factors of Suicides: A Retrospective Study - Suresh Kumar Karthikean; Kancharla Suresh Reddy; T. Sudharson; Veena Raja (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: “Suicide” is a fatal act that represents the person’s wish to die. The “psychological autopsy”is a “procedure for investigating a person’s death by reconstructing what the person thought, felt and didpreceding his or her death. The present study aimed to find out the profile of those completing suicide withregard to various factors to know the circumstances leading to suicide. Materials and method: Retrospectivediagnoses of psychiatric disorders were made by questions on 120 deceased cases of suicides, over the agesof 15 years, both urban and rural, which were sent for medical autopsy. All these data was collected byinterviewing the close relatives and friends of the patient. Results: Most of people involved in suicide weremales belonging to age group 16-30 years while very few of them were above 60 years. Most of them wereilliterates, working as daily labourers or self employed. Among women most of them were housewives.They were from low economic background, from the rural areas and married. The most common cause ofsuicides was financial loss, stress and illness. Conclusion: Proper counselling and monitoring the intendedvictims may help to reduce the number of deaths. Also the families need to be counselled regarding theimportance of family values and integrity among the family members.